Calculus 10th Edition

Published by Brooks Cole
ISBN 10: 1-28505-709-0
ISBN 13: 978-1-28505-709-5

Chapter 2 - Differentiation - 2.3 Exercises: 125

Answer

$x^3(\dfrac{2}{x^3})+2x^2(-\dfrac{1}{x^2})=2-2=0.$

Work Step by Step

Using the Power Rule: $f'(x)=-\dfrac{1}{x^2}$ Using the Power Rule: $f''(x)=\dfrac{d}{dx}f'(x)=\dfrac{2}{x^3}.$ $x^3(\dfrac{2}{x^3})+2x^2(-\dfrac{1}{x^2})=2-2=0.$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.